2022
DOI: 10.1038/s41467-022-30819-1
|View full text |Cite|
|
Sign up to set email alerts
|

Steering surface reconstruction of copper with electrolyte additives for CO2 electroreduction

Abstract: Electrocatalytic CO2 reduction to value-added hydrocarbon products using metallic copper (Cu) catalysts is a potentially sustainable approach to facilitate carbon neutrality. However, Cu metal suffers from unavoidable and uncontrollable surface reconstruction during electrocatalysis, which can have either adverse or beneficial effects on its electrocatalytic performance. In a break from the current catalyst design path, we propose a strategy guiding the reconstruction process in a favorable direction to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 67 publications
(64 reference statements)
1
62
0
Order By: Relevance
“…Our recent work demonstrated that ethylenediamine tetramethylenephosphonic acid (EDTMPA) molecules preferentially adsorb on Cu (110) during the CO 2 RR, inducing the selective generation of Cu (110) facets with an intrinsically high *CO binding strength (Fig. 3f, g) [39]. These studies demonstrate that the adsorption of intermediates or electrolyte additives on the catalyst surface can induce the formation of specific crystal facets with high activity; these facets are beneficial for the adsorption and conversion of intermediates.…”
Section: Crystal Facetsmentioning
confidence: 81%
See 3 more Smart Citations
“…Our recent work demonstrated that ethylenediamine tetramethylenephosphonic acid (EDTMPA) molecules preferentially adsorb on Cu (110) during the CO 2 RR, inducing the selective generation of Cu (110) facets with an intrinsically high *CO binding strength (Fig. 3f, g) [39]. These studies demonstrate that the adsorption of intermediates or electrolyte additives on the catalyst surface can induce the formation of specific crystal facets with high activity; these facets are beneficial for the adsorption and conversion of intermediates.…”
Section: Crystal Facetsmentioning
confidence: 81%
“…Reproduced with permission from Ref. [39]. Copyright 2022 Springer Nature examined by thermal desorption spectroscopy.…”
Section: Unsaturated Coordination Atomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Functionalizing the Cu surface with molecular modifiers has also been attempted in vaporfed systems. 23,27,43,80,96,97 would likely be possible to take some of the functionalized catalysts from aqueous-phase experiments and incorporate them into a GDE setup, or to do a similar data analysis for already existing experimental articles with a functionalized Cu surface in a vapor-fed environment as we have here done for systems in aqueous solution, 23,27,43,80,96,97 there is a great need for benchmarking with regards to GDE systems. This is especially true in terms of intrinsic activity for a similar CO 2 RR data analysis as we have done here to be performed on GDEs.…”
Section: Falsification Of Modifier Mechanismsmentioning
confidence: 99%